2018
DOI: 10.1155/2018/6939827
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Coal Swelling Deformation Caused by Carbon Dioxide Adsorption Based on X-Ray Computed Tomography

Abstract: The geologic sequestration of carbon dioxide by coal beds leads to the swelling deformation of coal. In order to investigate the swelling deformation characteristics at the microscopic scale, X-ray computed tomography (CT) scanning technology was used. X-ray CT scanning technology detects the internal structure, deformation, and porosity of coal at different gas pressures. Results show that swelling deformation is nonuniform, which is caused by the heterogeneity of the coal structure. Through quantitative meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The adsorption of gas leads to a decrease in the strength of coal samples [37], which can be reflected in the variation of the V P and V S . Figure 6, it can be seen that components of V P and V S of the coal samples are very different in the three directions, and meanwhile, their degree of decline varies from one another as the gas pressure increases.…”
Section: Test Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The adsorption of gas leads to a decrease in the strength of coal samples [37], which can be reflected in the variation of the V P and V S . Figure 6, it can be seen that components of V P and V S of the coal samples are very different in the three directions, and meanwhile, their degree of decline varies from one another as the gas pressure increases.…”
Section: Test Results and Discussionmentioning
confidence: 99%
“…Previous studies [37][38][39][40] have shown that the adsorption and desorption of coal samples are physical phenomena. When the coal samples absorb gas, they undergo expansion.…”
Section: Variation In Ultrasonic Velocity Of Coal Samples Under Diffementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the sorption process of the other gas components in the mixture with high concentration e.g. ethane, propane or carbon dioxide may also cause the swelling of the coal matrix and decrease the permeability of the transport channels for propylene 4648 . The results of the tests displayed in Tables 3 and 4 indicate that with the increase of gas concentrations at the inlet of the sorption column, the amount of propylene adsorbed generally increases, while the amount of ethylene adsorbed changed irregularly.…”
Section: Resultsmentioning
confidence: 99%
“…Adsorption time, adsorption pressure, and the microstructure affect the swelling deformation of the coal matrix after gas adsorption, and the changes in the porosity and permeability of coal after adsorption are closely related to the gas pressure in the pores and fractures and the degree of coal matrix swelling deformation. By evaluating the internal microstructure of coal under different adsorption pressures using CT and simulating coal swelling deformation using the Avizo software, the results showed that, as the adsorption pressure of gas increases, the thickness of typical fractures in the coal decreases significantly (see Figure ), causing a negative exponential decrease in porosity and permeability. , The preswelling stage of the coal matrix shows a significant decrease in fracture length, followed by a substantial decrease in fracture width …”
Section: Dynamic Evolution Of Microstructure and Macroscopic Properti...mentioning
confidence: 99%